Comparison of visual quality after wavefront-guided LASIK in patients with different levels of preoperative total ocular higher-order aberrations: a retrospective study - Zhang,Yu; Du,Yangrui; He,Ming; Zhang,Youdan; Du,Zhiyu (PeerJ, 2024)
Purpose To compare the visual quality after wavefront-guided femtosecond LASIK (WFG FS-LASIK) in patients with different levels of preoperative total ocular higher-order aberrations to guide clinical decision-making regarding patient selection and treatment strategies. Methods This study included 112 right eyes of 112 patients who previously underwent WFG FS-LASIK for correcting myopia and myopic astigmatism. The patients were divided into two groups based on the mean values of preoperative total ocular HOAs (0.30 ± 0.09 µm): HOA ≤ 0.3 and > 0.3 groups. The visual acuity, manifest refraction, corneal Strehl ratio (SR), root mean square (RMS) of corneal and ocular aberrations, and area under the log contrast sensitivity function (AULCSF) of both groups were compared preoperatively and at 1, 3, 6, and 12 months postoperatively. Results The induced ocular HOAs and coma (Δ = 1 mo − Preop) were significantly lower in the HOAs > 0.3 group than in the HOAs ≤ 0.3 group (ΔHOAs: 0.39 ± 0.19 vs. 0.29 ± 0.18 μm, t = 2.797, P = 0.006; Δ coma: 0.30 ± 0.19 vs. 0.20 ± 0.21 μm, t = 2.542, P = 0.012). In the HOAs > 0.3 group, ΔHOAs were negatively correlated with the preoperative ocular HOAs (r = −0.315, P = 0.019). In the HOAs ≤ 0.3 group, the regression equation for Δ HOAs = 0.098 + 0.053 |SE| (F = 21.756, P < 0.001). In the HOAs > 0.3 group, the regression equation for ΔHOAs = 0.534 − 1.081 HOAs + 0.038|Sphere| (F = 7.954, P = 0.001). The postoperative uncorrected distance visual acuity, spherical equivalent, corneal aberrations, SR and AULCSF of both groups were similar (all P > 0.05). Furthermore, the ocular aberrations were not significantly different between both groups at 3, 6, and 12 months postoperatively (all P > 0.05). In addition, compared with the preoperative period, the AULCSF of both groups were significantly increased in the postoperative period (all P < 0.05). Conclusions The induced ocular HOAs and coma in HOAs > 0.3 group were lower. However, both groups achieved equivalent and excellent visual quality after WFG FS-LASIK. WFG FS-LASIK may provide significant visual benefits for a wider range of patients.
Keywords: Wavefront-guided; FS-LASIK; Higher-order aberrations; Visual quality; Contrast sensitivity